Usage of Natural Uranium in Nuclear Reactors - A. V. Goncharuk (Глобальная ядерная безопасность)
The paper reviews the modern tendencies in the development of the world nuclear energy sector and progress in research of renewable energy technologies. Due to the unique advantages of the nuclear energy generation it proves to be very prospective source of power for the countries with a very intensive pace of development and huge energy demands. The main part of the article goes through the physical and economic backgrounds of the uranium fuel usage. The basics of the into-core processes and nuclear reactions substance are described. The comparative assessment of some aspects of thermal neutron and fast neutron technologies is listed. The physical background behind the two different reactor types builds up the conclusion on the potential advantages for the fuel basis of the atomic energy due to high involvement of the fast neutron specter into the nuclear energy generation processes